Pre-Clinical Development of a Humanized Anti-CD47 Antibody with Anti-Cancer Therapeutic Potential - Liu, Jie; Wang, Lijuan; Zhao, Feifei; Tseng, Serena; Narayanan, Cyndhavi; Shura, Lei; Willingham, Stephen; Howard, Maureen; Prohaska, Susan; Volkmer, Jens; Chao, Mark; Weissman, Irving L.; et al. (PLOS ONE, 2015)
CD47 is a widely expressed cell surface protein that functions as a regulator of phagocytosis mediated by cells of the innate immune system, such as macrophages and dendritic cells. CD47 serves as the ligand for a receptor on these innate immune cells, SIRP-alpha, which in turn delivers an inhibitory signal for phagocytosis. We previously found increased expression of CD47 on primary human acute myeloid leukemia (AML) stem cells, and demonstrated that blocking monoclonal antibodies directed against CD47 enabled the phagocytosis and elimination of AML, non-Hodgkin’s lymphoma (NHL), and many solid tumors in xenograft models. Here, we report the development of a humanized anti-CD47 antibody with potent efficacy and favorable toxicokinetic properties as a candidate therapeutic. A novel monoclonal anti-human CD47 antibody, 5F9, was generated, and antibody humanization was carried out by grafting its complementarity determining regions (CDRs) onto a human IgG4 format. The resulting humanized 5F9 antibody (Hu5F9-G4) bound monomeric human CD47 with an 8 nM affinity. Hu5F9-G4 induced potent macrophage-mediated phagocytosis of primary human AML cells in vitro and completely eradicated human AML in vivo, leading to long-term disease-free survival of patient-derived xenografts. Moreover, Hu5F9-G4 synergized with rituximab to eliminate NHL engraftment and cure xenografted mice. Finally, toxicokinetic studies in non-human primates showed that Hu5F9-G4 could be safely administered intravenously at doses able to achieve potentially therapeutic serum levels. Thus, Hu5F9-G4 is actively being developed for and has been entered into clinical trials in patients with AML and solid tumors (ClinicalTrials.gov identifier: NCT02216409).